Enhanced Antioxidative Defense by Vitamins C and E Consumption Prevents 7-Day High-Salt Diet-Induced Microvascular Endothelial Function Impairment in Young Healthy Individuals - Lidija Barić (Journal of Clinical Medicine, 2020)
This study aimed to examine whether the oral supplementation of vitamins C and E during a seven-day high salt diet (HS; ~14 g salt/day) prevents microvascular endothelial function impairment and changes oxidative status caused by HS diet in 51 (26 women and 25 men) young healthy individuals. Laser Doppler flowmetry measurements demonstrated that skin post-occlusive reactive hyperemia (PORH), and acetylcholine-induced dilation (AChID) were significantly impaired in the HS group, but not in HS+C+E group, while sodium nitroprusside-induced dilation remained unaffected by treatments. Serum oxidative stress markers: Thiobarbituric acid reactive substances (TBARS), 8-iso prostaglandin-F2α, and leukocytes’ intracellular hydrogen peroxide (H2O2) production were significantly increased, while ferric-reducing ability of plasma (FRAP) and catalase concentrations were decreased in the HS group. All these parameters remained unaffected by vitamins supplementation. Matrix metalloproteinase 9, antioxidant enzymes Cu/Zn SOD and glutathione peroxidase 1, and leukocytes’ intracellular superoxide production remained unchanged after the protocols in both HS and HS+C+E groups. Importantly, multiple regression analysis revealed that FRAP was the most powerful predictor of AChID, while PORH was strongly predicted by both FRAP and renin-angiotensin system activity. Hereby, we demonstrated that oxidative dis-balance has the pivotal role in HS diet-induced impairment of endothelial and microvascular function in healthy individuals which could be prevented by antioxidative vitamins consumption.